The internationalisation of cctv surveillance: Effects on crime and implications for emerging technologies - Thomas, Amanda L. (International journal of comparative and applied criminal justice, 2022)
In the last two decades, closed-circuit television (CCTV) surveillance cameras have come to occupy a central role in contemporary crime prevention across the world. Widely viewed as the “internationalization” of CCTV surveillance, there has been a corresponding growth in the evidence base about its effect on crime. The cumulative evidence demonstrates that CCTV surveillance is associated with significant yet modest reductions in crime and the effects vary across a range of contextual factors, including country of origin. This paper reports on the global expansion of CCTV schemes and examines – using systematic review methods with meta-analytic techniques – effects of CCTV schemes on crime in different countries. It draws upon a recently updated database of CCTV evaluations (N = 162) covering nearly five decades of research and spanning the globe, which now includes many industrialised countries. Implications for policy and research are discussed, with a special emphasis on emerging surveillance technologies.